Training Methods for Javelin Throwing Skills : Literature Review - Mappanyukki, Andi Atssam; Haeril, Haeril; Aksir, Muh Ilham (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore various effective training methods for improving javelin-throwing skills. Through a literature review, it was found that methods such as strength training, plyometric, and automatic recognition techniques showed positive results in improving athlete performance. Additionally, factors such as flexibility and muscle strength also contribute significantly to javelin throwing ability. The results of this study are expected to provide guidance for coaches and athletes in designing more effective training programs, as well as be the basis for further research on the development of javelin throwing training methods in the future.